Synthesis and Characterization of the Microstructure and Functional Group Bond of Fe3o4 Nanoparticles from Natural Iron Sand in Tobelo North Halmahera - Malega, Ferni; Indrayana, I Putu Tedy; Suharyadi, Edi (Jurnal Ilmiah Pendidikan Fisika Al-Biruni, 2018)
The Fe3O4 nanoparticles have been successfully synthesized from natural iron sand by using co-precipitation method at a temperature of 56oC. The elemental identification, structural characterization, and bonding analysis were carried out using XRF, XRD, and FTIR, respectively. The sample nanoparticles contain elements of Al, P, Ca, Ti, V, Cr, Mn, Ni, Cu, Zn, Rb, Re, Bi, and Fe. The composition of Fe element is 87.37%. The sample of the nanoparticle exhibited as the Fe3O4 which was shown by the diffraction pattern that belongs to a cubic spinel structure of Fe3O4. The crystallite size of the nanoparticle is 42.25 ± 0.42 nm. The lattice parameter was found at 8.384 ± 0.049 Å. The crystallite density is 5.232 103 kg/m3 while the lattice strain is 1.413 10-3/line. The FTIR spectra confirm that the existence of Fe-O stretching vibration in the range frequency of 658 cm-1-506 cm-1